Association of genetic variation of the six gene prognostic model for castration‐resistant prostate cancer with survival. Issue 1 (23rd August 2018) - Xie, Wanling; Stopsack, Konrad H.; Drouin, Sarah J.; Fu, Henry; Pomerantz, Mark M.; Mucci, Lorelei A.; Lee, Gwo‐Shu M.; Kantoff, Philip W.
Abstract : Background: We previously identified a blood RNA transcript‐based model consisting of six immune or inflammatory response genes ( ABL2, SEMA4D, ITGAL, C1QA, TIMP1, and CDKN1A ) that was prognostic for survival in cohorts of men with castration‐resistant prostate cancer (CRPC). We investigated whether inherited variation in these six genes was associated with overall survival (OS) in men with CRPC. Methods: The test cohort comprised 600 patients diagnosed with CRPC between 1996 and 2011 at Dana‐Farber Cancer Institute. Genotyping of 66 tagging single nucleotide polymorphisms (SNPs) spanning the six genes was performed on blood derived DNAs. For the top four SNPs ( P < 0.05), validation was conducted in an independent cohort of 223 men diagnosed with CRPC between 2000 and 2014. Multivariable Cox regression adjusting for known prognostic factors estimated hazard ratios (HR) and 95% confidence intervals (CI) of the association of genetic variants with OS. Results: Two thirds of patients in both cohorts had metastases at CRPC diagnosis. Median OS from CRPC diagnosis was 3.6 (95%CI 3.3‐4.0) years in the test cohort and 4.6 (95%CI 3.8‐5.2) years in the validation cohort. Fifty‐nine SNPs in Hardy‐Weinberg equilibrium were analyzed. The major alleles of rs1318056 and rs1490311 in ABL2, and the minor alleles of rs2073917 and rs3764322 in ITGAL were associated with increased risk of death in the test cohort (adjusted‐HRs 1.27–1.39; adjusted‐p <0.05; false discovery rate <0.35). In the validation cohort, a similar association with OS was observed for rs1318056 in ABL2 (adjusted‐HR 1.44; 95%CI 0.89‐2.34) and rs2073917 in ITGAL (adjusted‐HR 1.41; 95%CI 0.82‐2.42). The associations did not reach statistical significance most likely due to the small sample size of the validation cohort (adjusted‐p = 0.142 and 0.209, respectively). Additional eQTL analysis indicated that minor alleles of rs1318056 and rs1490311 in ABL2 are associated with a lower ABL2 expression in blood. Conclusions: These findings corroborate our initial work on the RNA expression of genes involved in immunity and inflammation from blood and clinical outcome and suggest that germline polymorphisms in ABL2 and ITGAL may be associated with the risk of death in men with CRPC. Further studies are needed to validate these findings and to explore their functional mechanisms.